Spatial interpolation of soil physico-chemical properties in major growing area of cumin and coriander based cropping system - AISHWATH, O.P.; JANGIR, C.K.; MEENA, M.D.; Y., RAVI; VISHAL, M.K.; CHAUDHARY, N. (Journal of Soil and Water Conservation, 2026)
Soil formation factors and process provide an insight for spatial variability of soil physical and chemical properties and at places if got influenced by anthropogenic activities. The goal of this study was to apply to use descriptive and geostatistical methods to quantify the spatial variability of 148 soil samples collected from 4 seed spices growing regions for soil physico-chemical properties, viz. pH, organic carbon, EC, available N, P, K, Cu, Fe, Mn, Zn, exchangeable Na, CEC, and particle size classes. The coefficient of variation for soil pH was the lowest (5%), while EC had the large variation (151%). The soil’s texture triplet (4-3-0), which consists of four (coarse fractions), three (moderate) fractions, and none (fine fraction), was estimated using information entropy (IE). The spatial correlation of soil Zn, Mn and Cu followed a spherical model among the several semi-variogram while DTPA - Fe showed an exponential model. The nugget: sill ratio for geostatistical analysis ranges from 0% for soil DTPA - Mn and Cu to 66% (DTPAFe). Cross-validation data on prediction errors showed that ordinary kriging (r = 0.891, P < 0.01) was superior to inverse distance weighting (r = 0.821, P < 0.01) for interpolating these micronutrients. The findings indicated that it is possible to apply the chosen fit model in any eco-regions for micronutrient cations of diverse origin.